2021
DOI: 10.3390/en14196192
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Convective Analyses of the PbLi Flow for the EU-WCLL Fusion Breeding Blanket

Abstract: The Water Cooled Lithium Lead (WCLL) breeding blanket is one of the driver blanket concepts under development for the European Demonstration Reactor (DEMO). The majority of the blanket volume is occupied by flowing PbLi at eutectic composition. This liquid metal flow is subdued to high fluxes of particles coming from the plasma which are translated into a high non-homogeneous heat volumetric source inside the fluid. The heat is removed from the PbLi thanks to several water tubes immersed in the metal. The dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The maximum temperature at the PbLi/EUROFER interface was found to be 580 °C (Figure 17), slightly above the temperature limit. The second group of analyses were dedicated to the frontal region of the BZ, close to the FW [31]. These needed to include buoyancy interactions since it is expected that they play a major role in this region.…”
Section: Vicinitymentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum temperature at the PbLi/EUROFER interface was found to be 580 °C (Figure 17), slightly above the temperature limit. The second group of analyses were dedicated to the frontal region of the BZ, close to the FW [31]. These needed to include buoyancy interactions since it is expected that they play a major role in this region.…”
Section: Vicinitymentioning
confidence: 99%
“…This was done because it was found that, with the employed mesh, it was hard to preserve stability and charge conservation for Ha values higher than 3000. The second group of analyses were dedicated to the frontal region of the BZ, close to the FW [31]. These needed to include buoyancy interactions since it is expected that they play a major role in this region.…”
Section: Vicinitymentioning
confidence: 99%
“…Dedicated CFD analyses have also been conducted to characterize the magnetoconvective regime in the OB equatorial elementary cell considering an idealized pipe layout (straight toroidal tubes) [27]. Compared to previous studies [28,29], the present model aimed to investigate the effect of a skewed magnetic field, more accurate FW thermal boundary conditions and higher magnetic field intensity (≈4 T, Ha = 9159).…”
Section: This Studymentioning
confidence: 99%